Pandangan Ulama Woyla Terhadap Ayat-Ayat Kepemimpinan Perempuan - Ainal Marziah; Hanif Hanif; Triansyah Fisa (Prodi Ilmu Al-Qur'an dan Tafsir, 2025)
The belief that women are weak and inferior has been a long-standing discussion in the Woyla community, leading to the perception that women are unfit for leadership, much like the classical scholars who largely prohibited women from leading. However, most contemporary scholars allow female leadership, interpreting the same Qur'anic verses differently. This study focuses on the views of dayah scholars in Woyla, Aceh Barat, aiming to explore their stance on female leadership and whether the Qur'an explicitly addresses this issue. Field research reveals that the majority of dayah scholars in Woyla hold that women should not be leaders, citing Surah An-Nisa, verse 34, as a basis for their argument. Nonetheless, they allow women to lead in specific areas outside of household and family matters, relying on Qur'anic verses that emphasize human equality and the mutual support of individuals without distinguishing between male and female. This nuanced understanding shows that while traditional views may restrict women’s leadership in certain domains, there is space for female leadership in other contexts based on broader interpretations of equality in the Qur’an.